Direct Lateral Window Approach Sinus Augmentation Procedure - Dragoș Virvescu; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2012)
The aim of the present study was to assess long-term changes in sinus-graft height after maxillary sinus floor augmentation. A total of 32 patients who underwent maxillary sinus floor augmentation were radiographically followed for up to about 2 years. The dental implants were applied in each case 6 months after the sinus augmentation. A 2:1:1 mixture of autogenous bone and bovine xenograft (PepGenP15 and PepGenFlow) was used as the graft material. Sinus-graft height was measured using 72 panoramic images immediately after augmentation and up to 24 months subsequently. Changes in sinus-graft height were calculated with respect to the marker diameter, the implant length and original sinus height. After 2 years, the grafted sinus floor was level with or slightly below the implant apex. This relationship was maintained over the long term. Sinus-graft height decreased significantly and approached original sinus height. The clinical survival rate of implants was 94.2%. All implant losses occurred within 2 years after augmentation. We conclude that progressive sinus pneumatization occurs after augmentation with a 2:1:1 autogenous bone/xenograft mixture of PepGenP15 and PepGenFlow, and long-term stability of sinus-graft height represents an important factor for implant success.